WHAT SHAPES HIGH ACCEPTANCE – MORAL ORIENTATION AND PSYCHOLOGICAL FLEXIBILITY - Kvitsiani, Mariam; Mestvirishvili , Maia (Georgian Psychological Journal, 2022)
The aim of this study was to examine the relationship between moral orientation types and the level of acceptance. Besides, the issue was to identify value systems on which moral types are built and their role in structuring acceptance. In the third part of the study, we describe a presumable mech- anism, which might affect the relationship between moral orientation types and level of acceptance. Data were obtained from 370 participants. Results indicated, that high level of moral absolutism (Situationism, Absolutism) related to self-transcendence and conservation value systems, while high moral relativism was associated to – openness to change. Logistic regression detected, that conser- vation value system is the strongest predictor of orientation type. Other than that, results suggest, that psychological ﬂexibility closely relates to basic value systems. Multiple hierarchical regression demonstrated the role of self-transcendence and openness to change as for psychological ﬂexibility, as well as for unconditional self-acceptance. Path analysis indicated that psychological ﬂexibility acted as partial mediator between basic value systems and unconditional self-acceptance. However, there was no connection between moral orientation type and acceptance. The theoretical implication of this study is to support a newer vision of moral psychology and to help to identify the basics and outcomes of moral orientation. The practical implication concerns to almost all therapeutic processes, which are oriented on growth of unconditional self-acceptance, and as such, it is important to consider every aspect of its constitutive.